Occupation and educational inequalities in laryngeal cancer: the use of a job index - Santi, Irene; Kroll, Lars Eric; Dietz, Andreas; Becher, Heiko; Ramroth, Heribert (BMC public health, 2013)
Previous studies tried to assess the association between socioeconomic status and laryngeal cancer. Alcohol and tobacco consumption explain already a large part of the social inequalities. Occupational exposures might explain a part of the remaining but the components and pathways of the socioeconomic contribution have yet to be fully disentangled. The aim of this study was to evaluate the role of occupation using different occupational indices, differentiating between physical, psycho-social and toxic exposures and trying to summarize the occupational burden into one variable.
Gesehen am 31.01.2022